Energy for Sustainability Foundations for Technology, Planning, and Policy - Randolph, John (Island Press/Center for Resource Economics, 2018)
Despite a 2016-18 glut in fossil fuel markets and decade-low fuel prices, the global transformation to sustainable energy is happening. Our ongoing energy challenges and solutions are complex and multidimensional, involving science, technology, design, economics, finance, planning, policy, politics, and social movements. The most comprehensive book on this topic, Energy for Sustainability has been the go-to resource for courses. This new edition has been thoroughly revised and updated to inform and guide students and practitioners who will steer this transformation. Drawing on a combined 80 years of teaching experience, John Randolph and Gilbert Masters take a holistic and interdisciplinary approach. Energy for Sustainability can help techies and policymakers alike understand the mechanisms required to enable conversion to energy that is clean, affordable, and secure. Major revisions to this edition reflect the current changes in technology and energy use and focus on new analyses, data, and methods necessary to understand and actively participate in the transition to sustainable energy. The book begins with energy literacy, including patterns and trends, before covering the fundamentals of energy related to physics, engineering, and economics. The next parts explore energy technologies and opportunities in three important energy sectors: buildings, electricity, and transportation. The final section focuses on policy and planning, presenting the critical role of public policy and consumer and investor choice in transforming energy markets to greater sustainability. Throughout the book, methods for energy and economic analysis and design give readers a quantitative appreciation for and understanding of energy systems. The book uses case studies extensively to demonstrate current experience and illustrate possibilities.